2019
DOI: 10.1038/s41598-019-44653-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-diagnostic C-reactive protein and albumin predict survival in Chinese patients with non-small cell lung cancer: a prospective cohort study

Abstract: Non-small cell lung cancer (NSCLC) is the most commonly diagnosed lung cancer and is associated with poor prognosis. This study aimed to analyze if serum C-reactive protein (CRP), albumin (Alb), and CRP/Alb ratio could provide prognostic information in patients with NSCLC. 387 patients with primary NSCLC were included in this analysis. Cox proportional hazards regression was used to estimate hazard ratio (HR) and 95% confidence interval (CI) of death with adjustment for some potential confounders. The multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 42 publications
2
66
0
1
Order By: Relevance
“…Regardless, there is some debate as to whether in ammation-based serologic markers obtained from systemic circulating blood denote the degree of immune response at the local tumor. Whatever the reason, many research results strongly support the evidence that local immune response manifests adequate prognostic value [21]. These serologic markers, as well as imaging studies, may provide additional information concerning the tumor response to immunotherapy in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Regardless, there is some debate as to whether in ammation-based serologic markers obtained from systemic circulating blood denote the degree of immune response at the local tumor. Whatever the reason, many research results strongly support the evidence that local immune response manifests adequate prognostic value [21]. These serologic markers, as well as imaging studies, may provide additional information concerning the tumor response to immunotherapy in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 82%
“…Even though lower PD-L1 expression was signi cantly associated with HPD, these events sometimes occurred even in the patients with high PD-L1 expression. Furthermore, NLR and PLR, hematological indicators re ecting the changes of blood cell pattern, are a secondary local response to immunotherapy [21,22,31]. Hence, with the exception of CAR, serologic markers before immunotherapy have no clinical implication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that CRP may have signi cant proin ammatory effects by binding to ligands exposed on cells or other autologous structures as a result of infection, in ammation, and other pathologies and then triggering complement activation, eventually exacerbating tissue damage and leading to more severe disease. Previous studies reported that the CRP level was an independent factor that was predictive of a poor prognosis in patients with cardiovascular disease, non-small-cell lung cancer and gastric cancer [21][22][23]. A retrospective study by Li et al recently reported that an increase in the CRP level can be used as an indicator of disease progression in patients with COVID-19 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ALB has been found to suppress the cell cycle and progression of hepatocellular carcinoma [31] [32]. Recent lines of evidence have identified ALB as an independent prognostic indicator in various malignant tumors, including lung [33], breast [34], and gastric cancers [35].…”
Section: Discussionmentioning
confidence: 99%